2018
DOI: 10.1186/s12913-018-2859-6
|View full text |Cite
|
Sign up to set email alerts
|

Does a provider payment method affect membership retention in a health insurance scheme? a mixed method study of Ghana’s capitation payment for primary care

Abstract: BackgroundGhana introduced a National Health Insurance Scheme (NHIS) in 2003 applying fee-for-service method for paying NHIS-credentialed health care providers. The National Health Insurance Authority (NHIA) later introduced diagnosis-related-grouping (DRG) payment to contain cost without much success. The NHIA then introduced capitation payment, a decision that attracted complaints of falling enrolment and renewal rates from stakeholders. This study was done to provide evidence on this trend to guide policy d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…The first-generation cephalosporins are currently not covered by the National Health Insurance Scheme (NHIS), a health insurance scheme introduced to provide financial access to healthcare for all Ghanaian residents, a possible reason why they were not prescribed. Most of the clients who attend this facility have subscribed to the NHIS and were probably unwilling to pay for medicines that were not covered by this scheme [ 16 ]. In the era of antimicrobial resistance, it is important to limit the use of broad-spectrum antimicrobials and rather opt for limited-spectrum antimicrobials that are still efficacious.…”
Section: Discussionmentioning
confidence: 99%
“…The first-generation cephalosporins are currently not covered by the National Health Insurance Scheme (NHIS), a health insurance scheme introduced to provide financial access to healthcare for all Ghanaian residents, a possible reason why they were not prescribed. Most of the clients who attend this facility have subscribed to the NHIS and were probably unwilling to pay for medicines that were not covered by this scheme [ 16 ]. In the era of antimicrobial resistance, it is important to limit the use of broad-spectrum antimicrobials and rather opt for limited-spectrum antimicrobials that are still efficacious.…”
Section: Discussionmentioning
confidence: 99%
“…62,63 The access and financial protection provided by the scheme have improved health-seeking behaviors and reduced risky health behaviors such as self-medication among Ghanaians. 64 Though some studies 42,65 reported a positive attitude of providers towards service delivery, others 10 reported poor attitudes of providers. Use of traditional medicine was high amongst both insured and uninsured but had no association with insurance status.…”
Section: Service Deliverymentioning
confidence: 99%
“…Some of these have focused on subscribers’ perception [ 5 , 15 , 16 ] and determinants of enrolment [ 6 , 17 22 ]. Others have also investigated the retention of subscribers [ 23 ], reducing medical claims cost [ 24 ], sustainability of the scheme [ 25 ], equity in accessibility [ 26 28 ], variation in coverage [ 29 ], quality healthcare assessment [ 30 ] and trends in subscription [ 13 ]. Despite comprehensive research on the NHIS, none of these studies have, to the best of our knowledge, focused on the position of women as to whether NHIS is helping pregnant women in accessing health services or not.…”
Section: Introductionmentioning
confidence: 99%